The relationship between social media addiction and emotion regulation skills and sleep quality of university students (Annals of Medical Research, 2024)
Aim: In current study, we aimed to determine relationship between social media addictions, emotion regulation skills and sleep quality of university students.Materials and Methods: Research was conducted in descriptive design. The sample of study consisted of 450 university students. Personal information form, Social Media Addiction Scale (SMAS), Cognitive Emotion Regulation Questionnaire (CERQ) and Pittsburgh Sleep Quality Index (PSQI) were used to obtain the data.Results: The mean total score of the SMAS of the students is 97.33±26.78. Mean scores of sub-dimensions of CERQ "Self-Blame", "Acceptance", " Rumination", "Positive Refocusing", "Refocusing on Plan", "Positive Reappraisal ", " Putting into Perspective", " Catastrophising " and "Blaming Others" are respectively; 11.23±2.78, 11.85±2.80, 13, .32±3.17, 12.19±2.81, 13.78±3.24, 13.44±3.32, 12.36±2.90, 10.40±2.95, 10.61±2.97. The mean total score of was PSQI 7.91±3.01.Conclusion: It was found that 31.5% of university students are moderately addicted to social media and their sleep quality is poor. As social media addiction increases, sleep quality worsens.
Keywords: Emotion regulation skill; Sleep quality; Social media addiction